AN ANALYSIS OF COLLOQUIAL EXPRESSION IN 22 JUMP STREET MOVIES - Irma, Eusebya A; Sama, Gratiana; Separ, Fransiskus M (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2023)
This study aimed to find the types of colloquial expression in 22 Jump Street movie based on the theory proposed by Partridge, namely single word, clipped word, short picturesque, contraction, verb-adverb combination (compound words). This study used a qualitative descriptive method. The data in this study used observation method. The data is form words and phrase. The results of this study indicate that among the five types of colloquial expression proposed by Partridge there are 4 types of colloquial expression consist of 73 data found in 22 Jump Street movie, namely single word (21), clipped word (7), contraction (35), verb-adverb combination (compound word) (10)